Bit stream sampling for a behavioral-based apt caused anomalies detection - Henchiri, Mourad M.H.; Wani, Sharyar (IJEAIS, 2020)
LTE based networks, in a wireless connectivity, provide a high bit stream data transfer. Thus, communicating sensitive data within smart environment such the smart cities, due to the smart infrastructure, is a challenge that faces technological upgrades. This view is drawn upon an ad-hoc architecture. And since that the digital data is a commonly used solution for current technological era, our research is made on that. Through this research we come out with a proved prognostication in a welldesigned system, combining the strength of a two-party relationship; machine learning analytics standards, dedicated and customized hardware to our research. Since the physical study of the AI is not getting the increase and positive growth as it should be, while looking at the digital commercial industry, it is getting a strong positive growth in the scientific services. Here we have to define our constraints which are used to measure environmental changes in the pre-given parameters; isolated zones, flows of data, etc… Thus, the success of such research is a step forward in technology provided to Humanity.